Wideband Dual-Linear Polarized Magnetoelectric Dipole Antenna With Wide Beam-Width in H-Plane - Yuzhen Chen; Tao Wang; Wenbo Liu; Yong Liu; Darong Gao; Le Yang (IEEE Access, 2021)
In this paper, a unidirectional wideband dual-linear polarized magnetoelectric dipole antenna with wide beam-width in H-plane is proposed. The antenna is composed of two orthogonal modified $Γ $ -shaped feeding structures, four V-portions, two pairs of folded electric dipoles, four vertical walls, and a ground. The orthogonal structures realize two orthogonal linear polarizations. To obtain a wide beam-width in H-plane, an extra equivalent magnetic dipole is introduced by folding the arm of the electric dipole and fixing four interdigital vertical walls on the edges of the ground. By comparing with the conventional ME dipole, the proposed ME dipole antenna has a wider beam-width in H-plane and also keeps the wideband property. Furthermore, the working principle and a parameter study are analyzed in detail. Through simulation, the maximum 3-dB beam-width in H-plane is 214.03° and 212.16° for two polarizations, respectively. According to the measurement results, the overlapped relative bandwidth (VSWR< 1.5) is 66.7% (1.5 GHz - 3 GHz). The boresight gain varies from 2.5 dBi to 5.7 dBi. The simulated and measured radiation patterns show a stable unidirectional radiation property and agree well with each other.